Commentary to the Supreme Court decision of July 9th 2015, III KK 375/14 - Czerwińska, Dorota (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
In the commented decision the Supreme Court presented the view that recent amendments of legal provisions concerning presence of the accused during the main trial mean that infringements committed before July 1st 2015 lost the quality of absolute grounds for reversing the judgment. The author disagrees with this thesis. The commentary analyses the views on the possibility of validating deficient trial procedures (including the deficient main trial and the infringements listed as absolute grounds for reversing the judgment) expressed in earlier legal literature and jurisprudence. The author comes to the conclusion that validating highly defective trial procedures is possible before issuing the original judgments, impossible – after the judgment becomes final and doubtful – during appellate proceedings. In the concluding remarks the author points out that the Supreme Court in one of its recent judgments has already adopted a different stance than in the commented decision – and that the latter deserves merit.
Keywords: transitional provisions; absolute grounds for reversing the judgment; validation of deficient trial procedures